2008
DOI: 10.1097/sap.0b013e318056d6cc
|View full text |Cite
|
Sign up to set email alerts
|

Should Excised Keloid Scars Be Sent for Routine Histologic Analysis?

Abstract: These histology results suggest that, given a good clinical suspicion of keloid, it may be unnecessary to send specimens at excision for routine histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…18 However, this current study has shown that detailed histopathologic reporting on keloid scars may be important, with specific reporting of surgical excision margins and border characteristics as these are possible indicators of clinical prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…18 However, this current study has shown that detailed histopathologic reporting on keloid scars may be important, with specific reporting of surgical excision margins and border characteristics as these are possible indicators of clinical prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…by Gulamhuseinwala et al 1 and the letter that was sent by Wong et al in response to this article. 2 Gulamhuseinwala et al.…”
mentioning
confidence: 85%
“…2 Gulamhuseinwala et al. 1 reported their pathologic analyses of 568 scars, of which 458 (81%) were classified as "keloids," 60 (11%) as "acne keloidalis," 35 (6%) as "hypertrophic scars (HSs)," and 14 (2%) as "normal scars." There were no reported malignancies or dysplasias.…”
mentioning
confidence: 99%
“…One of the most important indicative information that leads to keloid scar diagnosis is the history of some form of injury prior to the appearance of the lesion [7]. Spontaneous keloid scars, that is, those keloidal lesions that develop without previous injury or surgery, are rare [8].…”
Section: Introductionmentioning
confidence: 99%